Energy-Sector Workforce Development in West Virginia Aligning Community College Education and Training with Needed Skills - Gonzalez, Gabriella C. (RAND Corporation, 2015)
The production of natural gas and gas liquids from shale in West Virginia has increased demand for workers in the energy sector. In 2013, the National Energy Technology Laboratory (NETL) asked RAND to work closely with the Community and Technical College System of West Virginia to develop a collaborative strategy for preparing the local talent pool for the energy-sector workforce. We developed ten recommended action items.